1985
DOI: 10.1007/bf00293292
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hepatic porphyria with delta aminolevulinate dehydrase deficiency: Immunologic characterization of the non-catalytic enzyme

Abstract: Immunoreactive delta-aminolevulinate dehydrase (ALA-D) was measured in lysates from two porphyric patients with ALA-D deficiency (enzyme activities were below 2% of the normal level). By using two different immunologic methods, we found a cross-reactive immunologic material (CRIM+) which corresponded to 20% and 33% of the control level. Therefore the molecular basis that accounts for the deficiency of ALA-D in these patients is a structurally modified enzyme. The methods used to determine the molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
3

Year Published

1987
1987
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
11
1
3
Order By: Relevance
“…The patient had ALAD activity less than 3% of normal controls, both in erythrocytes (8) and in lymphocytes (9). Immunochemical studies showed that the proband's cells contained 20% positive crossreactive immunological material (CRIM) (25), suggesting the existence of a structurally altered enzyme(s). Northern blot analysis using total RNA showed a normal size and a normal amount of ALAD mRNA (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The patient had ALAD activity less than 3% of normal controls, both in erythrocytes (8) and in lymphocytes (9). Immunochemical studies showed that the proband's cells contained 20% positive crossreactive immunological material (CRIM) (25), suggesting the existence of a structurally altered enzyme(s). Northern blot analysis using total RNA showed a normal size and a normal amount of ALAD mRNA (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies indicated that ALAD activity in the proband's cells was less than 3% ofnormal (8,9), which accounted for the marked elevation of urinary ALA excretion in him (4). ALAD protein content in the proband's cells was markedly reduced, but a significant amount of CRIM was also present, suggesting that a noncatalytic enzyme was expressed (25). In the original description ofthis patient (8), he was considered to be homozygous for ALAD deficiency, since ALAD activity in erythrocytes was extremely low (; 2%), and the parents and the siblings had enzyme activity in the range of 50% of normal (8).…”
Section: Discussionmentioning
confidence: 99%
“…The immunological characterization of the two patients of Doss showed a cross-reactive immunological material which corresponded to 20% and 33% of the control level (33). Therefore the molecular basis for the deficiency of aminolaevulinic acid dehydratase in these patients is a structurally modified enzyme (33).…”
Section: Discussionmentioning
confidence: 88%
“…In the patient of Thunell, the immunoreactive enzyme protein in the child's erythrocytes was decreased to 28% of the normal control, suggesting the presence of positive cross reactive material (34). These results suggest that in these cases, the aminolaevulinic acid dehydratase deficiency is associated with the production of a catalytically abnormal enzyme protein (33,34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation